Cocoa and Chocolate Products: The Sensory Characteristics That Affect Consumers’ Acceptance - Dyah Ayu Savitri; Setiyono; Gatot Subroto; Hasbi Mubarak Suud; Nurhayadatul Haliza; Noer Novijanto (Journal La Lifesci, 2022)
This review describes the sensory characteristics of some cocoa and chocolate products which will later determine the acceptance of consumer. Cocoa beans are widely used as raw materials in many industrial sectors such as in food industries, cosmetics, and pharmaceutical. It will be further processed into several cocoa and chocolate products which performed certain characteristics. Relating to consumer acceptance, consumer will determine the product quality based on human senses. The evaluation of product using human senses is quite challenging since it present a set of particular and advantageous tools. Sensory evaluation promotes the scientific utilization and analysis of these tools. The aim of sensory evaluation in cocoa and chocolate product evaluation is to provide the information of the accepted characteristics based on human senses, which finally will contribute to the best quality of product expected by consumers.